Barrande's stratigraphic concepts, palaeontological localities and tradition - comparison with the present state - Chlupac,I. (Journal of the Czech Geological Society, 1999)
The evolution of stratigraphic concepts of the Proterozoic, Cambrian, Silurian and Devonian in the central Bohemian Barrandian area is reviewed, starting with the classic works of Joachim Barrande and traced up to the present time. Barrande's palaeontological localities are listed with their original and present designations, stratigraphical assignments and comments (18 localities in the Cambrian, 63 sites in the Ordovician, 71 in the Silurian and 40 in the Devonian). The Barrande's tradition and popularity is commented and examples of his drawings in fieldbooks are presented.
Keywords: Stratigraphy; history; Neoproterozoic; Cambrian; Ordovician; Silurian; Devonian; palaeontological localities; J. Barrande; Barrandian area; Czech Republic